2010
DOI: 10.1007/s10762-010-9641-0
|View full text |Cite
|
Sign up to set email alerts
|

Fourier Transform Domain Analysis of High T c Superconducting Rectangular Microstrip Patch over Ground Plane with Rectangular Aperture

Abstract: A rigorous full-wave analysis in the Fourier transform domain is carried out in order to obtain the resonant frequencies and half-power bandwidths of the high T c superconducting rectangular microstrip patches over ground planes with rectangular apertures. To include the effect of the superconductivity of the microstrip patch in the full-wave analysis, a complex surface impedance is considered. This impedance is determined by using London's equation and the two-fluid model of Gorter and Casimir. The validity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…The complex conductivity σ of the superconducting film is determined by using London's equation and the model of Gorter and Gasimir as [9]:…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The complex conductivity σ of the superconducting film is determined by using London's equation and the model of Gorter and Gasimir as [9]:…”
Section: Theorymentioning
confidence: 99%
“…Efficiency can be improved by the use of superconducting patch [8,9]. Nevertheless, these investigations which include the rectangular, circular and annular patch, have found that the superconducting microstrip antenna suffers from inherently narrow bandwidth.…”
Section: Introductionmentioning
confidence: 99%
“…The second advantage is the frequency independent penetration depth, unlike the common conductor. This means that dispersion introduced in superconducting devices will be negligible up to frequencies as high as hundreds of gigahertz [4]. The third advantage is that liquid nitrogen cheaper than liquid helium, as a refrigerant, can be used for cooling the superconducting devices because high Tc superconductors have Tc above the boiling point of liquid nitrogen, 77 K [2].…”
Section: Introductionmentioning
confidence: 99%
“…There are many techniques [10][11][12] to enhance the bandwidth of conventional microstrip antennas. Bandwidth of antenna can be increased by designing the antenna with dielectric cover [13], where structures with substrate-superstrate are generally employed to improve the characteristics of the resonator, especially those of the antenna [14].…”
Section: Introductionmentioning
confidence: 99%